Noncoercive elliptic equations with discontinuous coefficients in unbounded domains. (November 2017) - Monsurrò, Sara; Transirico, Maria
Abstract: In this paper we study Dirichlet problems for noncoercive linear elliptic equations with discontinuous coefficients in unbounded domains. Exploiting a nonlinear approach, we achieve existence, uniqueness and regularity results.